2003
DOI: 10.1103/physrevb.67.205408
|View full text |Cite
|
Sign up to set email alerts
|

Electron injection in a nanotube: Noise correlations and entanglement

Abstract: Transport through a metallic carbon nanotube is considered, where electrons are injected in the bulk by a scanning tunneling microscope tip. The charge current and noise are computed both in the absence and in the presence of one dimensional Fermi liquid leads. For an infinite homogeneous nanotube, the shot noise exhibits effective charges different from the electron charge. Noise correlations between both ends of the nanotube are positive, and occur to second order only in the tunneling amplitude. The positiv… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
81
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 61 publications
(87 citation statements)
references
References 49 publications
1
81
0
Order By: Relevance
“…Moreover, a single TLL can have inhomogeneities: e.g., a contact between an interacting TLL and a Fermi-liquid lead, a key ingredient of most transport measurements, is often studied as an inhomogeneous TLL wire smoothly interpolating between interacting (TLL) and noninteracting (Fermi-liquid) regions or as a two-wire junction with the Luttinger parameter abruptly changing at the junction. [38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56] A junction of three quantum wires with different Luttinger parameters has been studied in the weak coupling regime. 21,[57][58][59] The experimental importance of junctions of TLL wires with generally unequal Luttinger parameters motivates an in-depth study of their properties, which is the main objective of the present paper.…”
mentioning
confidence: 99%
“…Moreover, a single TLL can have inhomogeneities: e.g., a contact between an interacting TLL and a Fermi-liquid lead, a key ingredient of most transport measurements, is often studied as an inhomogeneous TLL wire smoothly interpolating between interacting (TLL) and noninteracting (Fermi-liquid) regions or as a two-wire junction with the Luttinger parameter abruptly changing at the junction. [38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56] A junction of three quantum wires with different Luttinger parameters has been studied in the weak coupling regime. 21,[57][58][59] The experimental importance of junctions of TLL wires with generally unequal Luttinger parameters motivates an in-depth study of their properties, which is the main objective of the present paper.…”
mentioning
confidence: 99%
“…When an electron is injected in the bulk of a quantum wire at a given Fermi point, say, −k F , this gives rise to two counterpropagating pieces which carry charge f e and (1 − f )e, respectively, where f = (1 + g)/2 [8,9,10,11,12]. We have shown that the ratio between the asymmetry A S = (I L − I R )/I S and the two-terminal conductance G 2 in the almost equilibrium regime, where the applied bias voltages are small compared to k B T /e, allows to construct a novel dimensionless ratio reflecting the charge fractionalization phenomenon,…”
Section: Resultsmentioning
confidence: 99%
“…The difference with the case of a point-like tunnel coupling should be noted; in that case, the terms G θφ in Eq. (A.5) would not be there and as a result | I(x → 0) | = I S /2 and therefore on gets I(x → L) = I S /2 [12].…”
Section: A1 Small Keldysh Digestmentioning
confidence: 99%
See 2 more Smart Citations